2010
DOI: 10.1371/journal.pone.0009675
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rhythmic Auditory Stimulation on Gait in Parkinsonian Patients with and without Freezing of Gait

Abstract: Freezing of gait (FOG) in Parkinson's disease (PD) rises in prevalence when the effect of medications decays. It is known that auditory rhythmic stimulation improves gait in patients without FOG (PD-FOG), but its putative effect on patients with FOG (PD+FOG) at the end of dose has not been evaluated yet. This work evaluates the effect of auditory rhythmic stimulation on PD+FOG at the end of dose. 10 PD+FOG and 9 PD-FOG patients both at the end of dose periods, and 10 healthy controls were asked to perform seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
130
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(143 citation statements)
references
References 44 publications
8
130
0
5
Order By: Relevance
“…Rhythm is a powerful stimulus for activity and several studies have shown that therapies including rhythm are beneficial for patients with PD [6,[19][20][21][22]. In addition, it has been suggested that music may affect the reward system of the brain [23].…”
Section: Music As Therapy Has Been Used For Many Years As An Alternatmentioning
confidence: 99%
“…Rhythm is a powerful stimulus for activity and several studies have shown that therapies including rhythm are beneficial for patients with PD [6,[19][20][21][22]. In addition, it has been suggested that music may affect the reward system of the brain [23].…”
Section: Music As Therapy Has Been Used For Many Years As An Alternatmentioning
confidence: 99%
“…This system is able to reduce the number of freezing of gait from 76% to 80% and to reduce duration of 70%. Nevertheless, this efficiency should be improved through a rehabilitation program [17]. However, several constraints impose limits to its daily usage such as: external auditory stimuli (ambient noise, discussion with other person, etc.…”
Section: B Biofeedback Cueingmentioning
confidence: 99%
“…All the 7 PD+FOG displayed freezing during the whole walking task but in all of them FOG appeared when turning or starting walking, which are by far the most frequent types of FOG (Arias and Cudeiro, 2010;Giladi et al, 1992); recordings from turning were not included into the analysis.…”
Section: Data Processingmentioning
confidence: 99%